Análise socioambiental da Vila da Penha: subsídios da geotecnologia ao planejamento local - PINTO, Daiana Sthefanie Pinheiro (2022)
This work aims to show the changes that have taken place over time in Vila da Penha in the municipality of Maracanã, Pará. A socio-environmental analysis of the area is carried out, using the tools of geoprocessing, through the use of satellite images. The aim is to support the management and environmental planning actions of the extractive reserve (Resex), addressing the dynamics of local use and occupation from the perspective of environmental sustainability. For the development of the research, observation and field analysis were carried out, a questionnaire was applied to the residents of the village, and remote sensing data processing, in order to learn about the changes in the landscapes and analyze how the local population perceives the socio-environmental changes in that are inserted.